Influencing the Fate of Cardiac and Neural Stem Cell Differentiation Using Small Molecule Inhibitors of ALK5. (31st July 2018) - Zhong, Qixing; Laco, Filip; Liao, Mei-Chih; Woo, Tsung L.; Oh, Steve K.W.; Chai, Christina L.L.
Abstract : In this study, 50 tri-substituted imidazoles (TIs), which are analogs of the small molecules TA-01 and SB203580, were synthesized and screened for cardiomyogenic activities. Several TIs displayed cardiomyogenic activities when applied during the differentiation from days 3–5. The TIs did not affect the Wnt/β-catenin pathway during cardiomyogenesis and the likely mechanism of action is through the inhibition of ALK5 of the TGFβ pathway. Interestingly, these TIs promoted the neural differentiation of human pluripotent stem cells (hPSCs) with a similar potency to that of the dual SMAD inhibitors SB431542/LDN-193189 when dosed from days 1 to 9. The neural induction activities of the TIs correlated with their ALK5 inhibitory activities. This study reports the discovery of small molecule inhibitors of ALK5, which can promote the differentiation of hPSCs into cardiomyocytes or neural cells depending on the time of dosing, showing potential for the production of clinical-grade cardiac/neural cells for regenerative therapy.